Architecture effects on L-selectin shedding induced by polypeptide-based multivalent ligands - Liu, Shuang (2011)
Multivalent interactions between selectins and their ligands play key roles in mediating the rolling and tethering of leukocytes in the early steps of the inflammatory response, as well as in lymphocyte circulation. L-selectin shedding, which is the proteolytic cleavage of L-selectin, can be induced by L-selectin clustering through the binding of multivalent ligands to multiple L-selectin molecules, and it has been shown to regulate leukocyte rolling and subsequent integrin activation for firm adhesion. In this paper, we report the production of homogenous glycopolypeptides modified with a 3,6-disulfo-galactopyranoside equipped with a caproyl linker. The saccharide residue was chemically attached to various polypeptide backbones of differing architectures; the composition and purity of the sulfated glycopolypeptides was confirmed via (1)H-NMR spectroscopy, amino acid analysis (AAA), and electrophoretic analysis. The retention of the conformation of the polypeptide backbone was confirmed via circular dichroic spectroscopy. The shedding of l-selectin from the surface of Jurkat cells induced by these sulfated glycopolypeptides, determined via ELISA-based methods, varied based on differences in the architectures of the polypeptide scaffolds, suggesting opportunities for these strategies in probing cell-surface receptor arrays and directing cell signaling events.